2022
DOI: 10.1111/jne.13171
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear hormone receptors in demyelinating diseases

Abstract: Demyelination results from the pathological loss of myelin and is a hallmark of many neurodegenerative diseases. Despite the prevalence of demyelinating diseases, there are no disease modifying therapies that prevent the loss of myelin or promote remyelination. This review aims to summarize studies in the field that highlight the importance of nuclear hormone receptors in the promotion and maintenance of myelination and the relevance of nuclear hormone receptors as potential therapeutic targets for demyelinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 255 publications
0
5
0
Order By: Relevance
“…The thyroid hormones (T4 and T3) play an essential role in peripheral nerve regeneration producing a lasting and stimulatory action on axotomized neurons and Schwann cells ( Barakat-Walter, 1999 ). Limited data exist on their role in the development of demyelinating diseases (reviewed in Zorrilla Veloz et al, 2022 ). Disorders of thyroid metabolism are possible causes of inflammation and autoimmune reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The thyroid hormones (T4 and T3) play an essential role in peripheral nerve regeneration producing a lasting and stimulatory action on axotomized neurons and Schwann cells ( Barakat-Walter, 1999 ). Limited data exist on their role in the development of demyelinating diseases (reviewed in Zorrilla Veloz et al, 2022 ). Disorders of thyroid metabolism are possible causes of inflammation and autoimmune reactions.…”
Section: Discussionmentioning
confidence: 99%
“…As cholesterol efflux regulatory proteins, several members of ABC transporters including ABCA1, ABCG1/4/5/8 are transcriptionally regulated by LXRs [ 15 ]; these membrane transporters open the gate and translocate sterols outside of cells through conformational change after substrates bind and ATP drives the process [ 17 ]. Next, the combination with ApoE, the dominant apolipoprotein in brain controlled by LXRs, is necessary for the removal from or recycling in the CNS of the effluxed cholesterol [ 18 ]. Based on this ability to regulate multiple genes, LXRs localize in the nexus of cholesterol trafficking in the CNS, and its dysregulation thus leads to various neurodegenerative pathologies.…”
Section: Lxr In Lipid Homeostasismentioning
confidence: 99%
“…Estrogen receptors are expressed in both OPCs and oligodendrocytes (OLs), in vitro and in vivo , suggesting that estrogen signaling may play a role in regulating the proliferation, differentiation, and survival of these cells. Indeed, studies have shown that estrogen treatment can increase the number of oligodendrocytes and myelin production, in vitro and in vivo ( 90 ). In particular, estrogen receptors have been shown to play a role in promoting the differentiation of OPCs into mature oligodendrocytes.…”
Section: Estrogen Receptors and Oligodendrogenesismentioning
confidence: 99%